A variação no uso de artigo definido diante de possessivos prénominais no português falado em Luanda-Angola: uma análise sociolinguística - Azevedo, Matheus de Araujo (2025)
The variation in the use of the definite article accompanying possessives has been observed in Portuguese, with data from Brazilian Portuguese and European Portuguese (Silva, 1982; Castro, 2006; Floripi, 2008; Schei, 2009; Magalhães, 2011; Sedrins; Pereira; Silva, 2017; Brito, 2019). Previous research on this phenomenon allows for generalizations on the topic, such as the predominance of the definite article in the European variety and a variable behavior of the article among Brazilian speakers in possessive contexts. Given this, the present study examined the variable behavior of the definite article preceding prenominal possessives in an African variety, Portuguese spoken in Luanda, representing Angolan Portuguese, in order to contribute to the description of the usage norms of this non-European variety, as well as to investigate possible indications of the effect of language contact in its formation, which occurred in a setting of contact with Bantu languages. The investigation aimed to describe and analyze the omission of the definite article and its patterns of variation based on the theoretical and methodological principles of the Theory of Linguistic Variation and Change (Weinreich; Labov; Herzog, 2006 [1968]; Labov, 2008 [1972]). To this end, a corpus of oral data from the urban Luanda variety was used, collected through sociolinguistic interviews recorded in the Angolan capital in 2008 and 2013 with participants who declared Portuguese as their first or second language. This corpus belongs to the linguistic archive of the research project “In Search of the Roots of Brazilian Portuguese – Phase III”, located at the Center for Portuguese Language Studies at the State University of Feira de Santana. Through statistical analysis of the quantified data, the results revealed that the variability of the definite article preceding possessives in this speech community is conditioned by both linguistic factors—such as syntactic function, the presence or absence of a preposition and its type, noun type, and the gender and number of the noun phrase head—and social factors, such as age group and the speaker’s first language, with indications of structural transfer from Bantu languages to Portuguese. Moreover, in a continuum, the Angolan norm appears to align with the Brazilian norm, suggesting a possible convergence resulting from shared historical processes that shaped the phenomenon’s realization. Therefore, this study contributes to the research agenda investigating the sociolinguistic reality of African varieties of Portuguese, as well as expanding knowledge on the effects of language contact on Portuguese varieties